Natal origin and population connectivity of bigeye and yellowfin tuna in the Pacific Ocean - Rooker, Jay R.; David Wells, R. J.; Itano, David G.; Thorrold, Simon R.; Lee, Jessica M. (Fisheries oceanography, 2016)
Natural chemical markers (stable isotopes and trace elements) in otoliths of bigeye tuna (Thunnus obesus) and yellowfin tuna (T. albacares) were used to investigate their origin and spatial histories in the western and central Pacific Ocean (WCPO). Otolith chemistry of young‐of‐the‐year (YOY) T. obesus and T. albacares from four regions in the WCPO was first determined and used to establish baseline chemical signatures for each region. Spatial variation in stable isotope ratios of YOY T. obesus and T. albacares was detected, with the most noticeable difference being depleted otolith δ18O values for both species from the far west equatorial and west equatorial regions relative to the central equatorial and Hawaii regions. Elemental ratios in otoliths were also quantified for YOY T. obesus and T. albacares collected in 2008, and several showed promise for distinguishing YOY T. obesus (Mg:Ca, Mn:Ca, and Ba:Ca) and T. albacares (Li:Ca and Sr:Ca). The natal origin of age‐1 to age‐2+ T. obesus and T. albacares was then determined for two regions of the WCPO, and mixed‐stock analysis indicated that T. obesus and T. albacares in our west equatorial sample were almost entirely from local production, with a minor contribution from central equatorial waters. Similarly, T. albacares collected in Hawaii were exclusively from local sources; however, a large fraction of T. obesus in Hawaii were classified to the central equatorial region, suggesting that the movement of migrants from outside production zones (i.e., south of Hawaii) are important to Hawaii's domestic fishery.